Pengaruh Current Ratio (CR), Debt To Asset Ratio (DAR) dan Return On Equity (ROE) terhadap Price To Book Value (PBV) pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Rita Satria; Raha Dhita Prawita Sari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study was to determine the effect of Current Ratio (CR), Debt to Asset Ratio (DAR) and Return on Equity (ROE) on the Price to Book Value (PBV) in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2022 partially or simultaneously. The population in this study was 40 (forty) food and beverage sub-sector manufacturing companies. The number of samples that meet the criteria is 11 (eleven) companies with 5 years of observation. This research method is quantitative. The results of this research show that partially the Current Ratio (CR) variable has no significant effect on the Price to Book Value (PBV), the Debt to Asset (DAR) variable partially has a significant negative effect on the Price to Book Value (PBV), Return on Equity ( ROE) partially has a significant effect on Price to Book Value (PBV). Current Ratio (CR), Debt to Asset Ratio (DAR) and Return on Equity (ROE) simultaneously have a significant effect on the Price to Book Value (PBV).